Optimal cut-off values of visceral fat area for predicting metabolic syndrome among patients with ischemic stroke: a cross-sectional study - Lu, Xueyan; Wang, Jing; Sun, Huijie; Liu, Dandan; Yan, Xiuli; Liu, Zhuo (Frontiers in Neurology, 2024)
The prevalence of metabolic syndrome (MetS) among patients with ischemic stroke is relatively high. The visceral fat area (VFA) is a predictor of MetS. This study aimed to estimate sex-specific optimal cut-off values of VFA and MetS risk factors among patients with ischemic stroke.A cross-sectional study including 851 patients with ischemic stroke was conducted between March 2019 and January 2020 in a tertiary hospital in the northeast of China. VFA was measured using the dual bioelectrical impedance method. Binary logistic regression analysis was used to investigate MetS risk factors, and the VFA cut-off value was assessed using receiver operating characteristic curve analysis.The overall prevalence of MetS was 43.4%. After adjusting for potential confounders, female sex (odds ratio [OR] = 2.86, P < 0.001), the presence of visceral obesity according to VFA (OR = 7.45, P < 0.001), being overweight (OR = 2.75, P < 0.001) or obesity (OR = 6.00, P < 0.001) were associated with an increased risk of MetS. The correlation between VFA and MetS in patients with ischemic stroke was strongest with cut-off values of 104.3 cm 2 (sensitivity 73.0%, specificity 83.1%) for men, and 94.1 cm 2 (sensitivity 70.9%, specificity 72.9%) for women.MetS affected approximately a half of patients with ischemic stroke. Female sex, visceral obesity, and body mass index were independent risk factors for the development of MetS.Sex-specific reference values for VFA are proposed for the prediction of incident MetS in patients with ischemic stroke.